Post-cesarean section vaginal delivery - Romero, Karín (2015)
OBJETIVE: To evaluate the management of patients with a history of previous cesareada. DESIGN: Descriptive Method. LUGAR: Hospital IV Victor Lazarte Echegaray, EsSalud, Trujillo. MATERIAL AND METHODS: Patients undergoing cesarean section in the period May 1999 to April 2000. RESULTS: 1322 births were studied; of caesarean sections 618, 195 had a history of previous cesareada once, of which 97 were selected; of them, 40.2% were between 26 and 35 years. The most common causes of cesarean in previous cesareada were acute fetal distress (31.9%) and dysfunctional labor (28.9%). CONCLUSIONS: In patients with a history of previous cesareada, 46.4% ended in vaginal delivery and 53.6% by cesarean section.